If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -14 = -22 Reorder the terms: -14 + 3x = -22 Solving -14 + 3x = -22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 3x = -22 + 14 Combine like terms: -14 + 14 = 0 0 + 3x = -22 + 14 3x = -22 + 14 Combine like terms: -22 + 14 = -8 3x = -8 Divide each side by '3'. x = -2.666666667 Simplifying x = -2.666666667
| 3x-5=3x+3 | | x^2+9x+c=0 | | 8t^2-18t-5=0 | | 2.5y+12=5y | | v-1.3=75.2 | | x^2-7x+c=0 | | -3.36=6+5.12 | | 7+12x=69 | | 24x-32=24x-32 | | (2z/3z-9)-(z+1/2z-6) | | 2(x+3)+6=6x-4(-2+x) | | 5(3c-1)-6=13c+3 | | 2z/3z-9-z+1/2z-6 | | 3x-4x=19 | | (3x+6)/(5)=2x-3 | | 5=3/4(5x-4) | | 5y=15-4x | | 6m+16=4m+9 | | 5+2y-4-2y-4= | | 3z^3-300z=0 | | (6x-4)/(2x) | | p+7=39 | | 3(y-5)=18 | | -2/9(3/1-4/9) | | 9x+-2=1 | | -7a=6 | | 32x-6=25x | | 93-6x=30x+17 | | -18=12a | | (5)/(6)-(1)/(3)=3 | | y-(-9)=-2/9(3-4/9) | | 5=13t |